Marketing Strategy on PT. Aurora Wisata Internusa Medan During The Covid-19 Pandemic - Wilda Khairannur; Emrizal (Cita Konsultindo Research Center, 2021)
Marketing strategy is a very important part in the implementation of the company's overall strategy, especially in conditions of very tight competition. The Covid-19 pandemic had a significant impact on the decline in revenue at PT. Aurora Wisata Internusa Tour and Travel Medan. Determining the right marketing strategy is one way to keep business activities running. The type of research used is descriptive qualitative research which aims to find out, describe and reveal the actual situation related to the marketing strategy carried out by service companies. Data collection methods used are interview methods, observation methods and document collection methods. The analysis of the data used in this study consisted of several stages, namely the data reduction stage, the data presentation stage and finally drawing conclusions. The results showed that the service company PT. Aurora Wisata Internusa Tour and Travel Medan in running its business uses marketing strategies related to the marketing mix, namely product, price, place, promotion, people, physical evidence. and process